The inevitability of change in Madrasa curriculum in the view of Nadwatul Ulama - H.M. Ataur Rahman Nadwi (Bulletin of Islamic Research, 2025)
Religious schools have played a vital role in spreading and promoting the Arabic language worldwide. These institutions have nurtured generations of scholars, preachers, writers, and thinkers who have greatly influenced educational systems throughout history. Among the most prominent examples is Darul Ulum Nadwatul Ulama’ in Lucknow, India, which has long prioritized Arabic language education at various levels. The institution places great importance on developing proficiency in reading, writing, and teaching Arabic, understanding its significance not only as the language of the Qur’an and Hadith, but also as a key global language in today’s world. Arabic is essential in fields like law and religious studies, serving as a cornerstone for understanding legal sciences and divine laws. This study focuses on the evolution of Nadwa’s curriculum, particularly its shift from traditional approaches that struggled to connect students with both Islamic knowledge and proficiency in Arabic language and literature. Recognizing the changing demands of the modern era, Nadwa embarked on a series of reforms to update and enhance its educational programs. New textbooks were introduced, covering subjects like Arabic language and literature, the history of Arabic literature, pre-Islamic writings, and poetry, replacing outdated resources. Despite these changes, Nadwatul Ulama’ has continuously innovated its curriculum to adapt to the evolving needs of students and society. This paper seeks to explore Nadwa’s significant role in advancing the Arabic language and emphasizes the ongoing importance of continually revising educational curricula to meet the demands of the present age.